Implementation of Base Station as An Intermediary Referee Box in the delivery of Wheeled Football Robot Movement Commands - Marchiano Alfredo Fouk; Hudiono Hudiono; Aad Hariyadi (Jurnal Jaringan Telekomunikasi, 2022)
In the contest of Indonesian wheeled robot football or KRSBI wheeled robot which competes with wheeled football robots, there is a referee who controls the course of the match, the referee box. For referee box to provide commands that can set the course of the robot, a base station is required that serves to receive data from the referee box and translated and then sent it to the robot. The use of TCP socket programming is quite successful whereby 17 attempts to send commands from referee box can be accepted all by base station with a success rate of 100%. The use of robot operating system (ROS) to pass data in the form of coordinate points and commands for robots chasing balls or stops was also successfully carried out where from 17 attempts the delivery of orders, it can reach 100% success rate. After that, the measurement of distance analysis against quality of service (QoS) with 3 different distances, and obtained the following results, at a distance of 3 meters obtained an average delay of 44.41 ms, throughput of 767.29 kbps and no missing package, at a distance of 8 meters obtained an average delay of 7.22 ms, an average throughput of 1065.17 kbps and no missing packages, lastly at a distance of 15 meters obtained an average delay of 103.99 ms, an average throughput of 835.51 kbps and there was a missing package of 6.9% on 1 order so that the average lost package was obtained by 0.405%.